2022
DOI: 10.3399/bjgp.2022.0178
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for inappropriate proton pump inhibitor use: observational study in primary care

Abstract: Background: Proton pump inhibitor (PPI) indications are limited to gastrointestinal disorders and ulcer prophylaxis. Still, PPIs are among the most frequently prescribed drugs. Aim: To evaluate the appropriateness of PPI prescriptions and identify predictive factors for inappropriate PPI use. Design and Setting: Observational study using a Dutch primary care database with all new PPI prescriptions between 2016 and 2018. Methods: Individual patient data and details on PPI use were collected. Appropriateness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…More than half of PPIs prescribed among our patients were not clearly motivated. This evidence is in line with other papers 20,21 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…More than half of PPIs prescribed among our patients were not clearly motivated. This evidence is in line with other papers 20,21 …”
Section: Discussionsupporting
confidence: 94%
“…This evidence is in line with other papers. 20,21 In our cohort, concomitant PPI use seems to have a detrimental impact on PFS and OS, even if statistical significance is not reached. Two recent meta-analyses suggested that PPIs are significantly associated with poorer OS and PFS for cancer patients treated with ICIs.…”
Section: Discussionmentioning
confidence: 70%
“…Long-term PPI use should be avoided due to the risk of adverse effects, as recommended by several countries [30][31][32]. Infectious diseases, particularly, abdominal infections and pneumonia, are among the adverse effects also reported in patients with CKD [22,33].…”
Section: Proton Pump Inhibitor and Infection Inmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are one of the most commonly prescribed classes of drugs, but an estimated 25-70% of PPI users may not have an appropriate indication, depending on the clinical setting 1234. For such patients, PPIs cause unnecessary healthcare spending and pill burden.…”
Section: Introductionmentioning
confidence: 99%
“…Proton pump inhibitors (PPIs) are one of the most commonly prescribed classes of drugs, but an estimated 25-70% of PPI users may not have an appropriate indication, depending on the clinical setting. 1 2 3 4 For such patients, PPIs cause unnecessary healthcare spending and pill burden. Observational studies have also shown associations between PPIs and many medical conditions, including chronic kidney disease, fractures, pneumonia, cardiovascular disease, and Clostridium difficile infection, although only indirect evidence supports a causal link between PPIs and these conditions, with uncertain clinical significance.…”
Section: Introductionmentioning
confidence: 99%